PENGARUH PERAN KEPEMIMPINAN DAN BUDAYA ORGANISASITERHADAP MOTIVASI KERJA YANG BERDAMPAK PADA PENINGKATAN KINERJA PERANGKAT DESA DI KECAMATAN TELUKJAMBE TIMUR - Anirah . (Universitas Buana Perjuangan Karawang, 2018)
ABSTRACT This research aims to obtain empirical evidence and find clarity of phenomena and conclusions about the influence of leadership roles and organizational culture on work motivation that impact on improving the performance of Village Devices District of East Telukjambe. This thesis is expected to contribute to the development of management science, especially as a contribution of scientific literature in human resources management, as reference material in scientific writing, as information material, both for leaders and colleagues in Kecamatan Telukjambe Timur Karawang regency in the implementation of performance based management, as a material consideration and input in making decisions and determine the direction of policy. The research is done by using quantitative method with descriptive and verification method, that is collecting, presenting, analyzing and doing hypothesis testing, and making conclusion and suggestion. Based on the results of the research analysis, the following conclusions are obtained: The value of correlation coefficient between leadership variables and organizational culture is 0.595, Influence of leadership role to employee work motivation equal to 0,1616 or 16,16%. The influence of organizational culture on employee work motivation of 0.2504 or 25.04%. The influence of leadership role on employee performance is 0.0723 or 7.23%. While the influence of organizational culture on employee performance of 0.0230 or 2.30%. The influence of work motivation on employee performance of 0.7448 or 74.48%. Simultaneously the role of leadership and organizational culture significantly influence the work motivation of 41.20%. The rest of 58.80% is the influence that comes from other factors. Simultaneously the role of leadership and organizational culture has a significant effect on work motivation which impact on employee performance improvement equal to 84,01%. The rest of 15.99% is the influence that comes from other factors. Keywords: role of leadership, organizational culture, work motivation, employee performance